Cathepsin B‐mediated CD18 shedding regulates leukocyte recruitment from angiogenic vessels. Issue 1 (13th September 2017) - Nakao, Shintaro; Zandi, Souska; Sun, Dawei; Hafezi‐Moghadam, Ali
Abstract : Cathepsin B (CtsB) contributes to atherosclerosis and cancer progression by processing the extra‐cellular matrix and promoting angiogenesis. Although CtsB was reported to promote and reduce angiogenesis, there is no mechanistic explanation that reconciles this apparent discrepancy. CtsB cleaves CD18 from the surface of immune cells, but its contribution to angiogenesis has not been studied. We developed an in vivo technique for visualization of immune cell transmigration from corneal vessels toward implanted cytokines. Wild‐type (WT) leukocytes extravasated from limbal vessels, angiogenic stalks, and growing tip vessels and migrated toward the cytokines, indicating immune competence of angiogenic vessels. Compared to WT leukocytes, CtsB −/− leukocytes accumulated in a higher number in angiogenic vessels, but extravasated less toward the implanted cytokine. The accumulated CtsB −/− leukocytes in angiogenic vessels expressed more CD18. CD18 −/− leukocytes extravasated later than WT leukocytes. However, once extravasated, CD18 −/− leukocytes transmigrated more rapidly than their WT counterparts. These results suggest that, although CD18 facilitates efficient extravasation, outside of the vessel CD18 interaction with the extracellular matrix, it reduced transmigration velocity. Our results reveal an unexpected role for CtsB in leukocyte extravasation and transmigration, which advances our understanding of the complex contribution of CtsB to angiogenesis.— Nakao, S., Zandi, S., Sun, D., Hafezi‐Moghadam, A. Cathepsin B‐mediated CD18 shedding regulates leukocyte recruitment from angiogenic vessels. FASEB J. 32, 143‐154 (2018). www.fasebj.org